Tin-based perovskite thin film, preparation method thereof and tin-based perovskite solar cell

By using polyethylene derivatives to control crystallization and oxidation in the preparation of tin-based perovskite films, the problem of balancing film morphology and photoelectric properties is solved, achieving high-quality tin-based perovskite films and improved solar cell performance.

CN120603461APending Publication Date: 2025-09-05UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510735994.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

The existing technology for preparing tin-based perovskite films has problems with rapid crystallization and oxidation, resulting in poor film morphology and reduced photoelectric performance, making it difficult to optimize both surface morphology and photoelectric performance.

Method used

Polyethylene derivatives such as polyvinyl alcohol or polyvinyl pyrrolidone are dissolved in an organic solvent with tin-based perovskite raw materials, coated into a film by printing and annealing, and the crystallization rate and oxidation process are controlled to form a uniform and dense film.

Benefits of technology

The uniform and continuous surface morphology and excellent photoelectric conversion efficiency of tin-based perovskite films were achieved, the defect state density was reduced, and the film quality and device performance were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120603461A_ABST
    Figure CN120603461A_ABST
Patent Text Reader

Abstract

The invention provides a tin-based perovskite thin film, a preparation method thereof and a tin-based perovskite solar cell, and belongs to the technical field of photovoltaic materials. The preparation method comprises the following steps: dissolving a tin-based perovskite raw material in an organic solvent, and adding polyvinyl alcohol or polyvinylpyrrolidone to prepare a tin-based perovskite precursor solution; and coating the tin-based perovskite precursor solution through a printing method to form a film, and carrying out annealing treatment to obtain the tin-based perovskite thin film. According to the invention, polyvinyl alcohol or polyvinylpyrrolidone is used to slow down the crystallization rate of perovskite, and is used as a template to provide heterogeneous nucleation sites, so that the defect state density is reduced, and the compactness of the perovskite film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic materials, and in particular to a tin-based perovskite film and a preparation method thereof, and a tin-based perovskite solar cell. Background Art

[0002] Perovskite solar cells use metal halide semiconductor perovskites as the light-absorbing layer. They have the advantages of low raw material costs, relatively simple preparation processes, and excellent photoelectric conversion efficiency.

[0003] Currently, the majority of tin-based perovskite films are prepared by spin coating. Only a few printing methods, such as doctor blade coating and inkjet printing, are used. However, due to the relatively active 5S orbital electrons of the Sn element in the tin-based perovskite precursor material, these printing methods, compared to spin coating, are unable to use antisolvents. This leads to more pronounced problems such as rapid crystallization and oxidation during the preparation of tin-based perovskite films, resulting in poor morphology. Increasing the film thickness to improve the surface morphology results in a significant decrease in photocurrent.

[0004] Therefore, how to maintain the excellent surface morphology of tin-based perovskite films while achieving good optoelectronic properties has become an urgent problem to be solved. Summary of the Invention

[0005] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present invention provides a tin-based perovskite film and a preparation method thereof, and a tin-based perovskite solar cell.

[0006] According to an embodiment of one aspect of the present invention, a method for preparing a tin-based perovskite film is provided, comprising: dissolving a tin-based perovskite raw material in an organic solvent, and adding a polyethylene derivative to prepare a tin-based perovskite precursor solution, wherein the polyethylene derivative includes at least one of polyvinyl alcohol and polyvinyl pyrrolidone; and coating the tin-based perovskite precursor solution into a film by a printing method, and obtaining the tin-based perovskite film after annealing.

[0007] In some embodiments, the coating and annealing processes are performed under an inert atmosphere.

[0008] In some embodiments, the mass ratio of the polyethylene derivative to the tin-based perovskite raw material is 0.01-0.3:100.

[0009] In some embodiments, the tin-based perovskite raw materials further include formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride.

[0010] In some embodiments, the purity of iodine powder and tin powder is ≥99%.

[0011] In some embodiments, the molar ratio of formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride is 1:1:1:1:(0.01-0.2).

[0012] In some embodiments, dissolving the tin-based perovskite raw material in an organic solvent includes: dissolving the tin-based perovskite raw material in an organic solvent at a temperature of 15~35°C; the organic solvent includes N,N-dimethylformamide, dimethyl sulfoxide, and the organic solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, and γ-butyrolactone.

[0013] In some embodiments, the annealing temperature of the annealing treatment is 60-150° C., and the annealing time is 5-30 min.

[0014] According to another embodiment of the present invention, a tin-based perovskite film obtained by the above-mentioned preparation method is provided; preferably, the thickness of the tin-based perovskite film is 100-200 nm.

[0015] According to an embodiment of yet another aspect of the present invention, a tin-based perovskite solar cell is provided, comprising a light-absorbing layer, wherein the light-absorbing layer comprises the above-mentioned tin-based perovskite film.

[0016] According to the method for preparing the tin-based perovskite film provided by the above embodiment of the present invention, the polar groups in the polyethylene derivative, such as carbonyl and hydroxyl groups, can form coordination bonds with the ions in the tin-based perovskite precursor raw materials, and the steric hindrance provided by the long chain structure of the polyethylene derivative hinders the Sn from 2+ The migration and crystal growth of the polyethylene derivatives are stimulated, thereby reducing the crystallization rate. Simultaneously, the carbonyl and hydroxyl groups on the polyethylene derivatives form heterogeneous nucleation sites, inducing preferential nucleation of perovskite grains on their surfaces. This disperses the nucleation sites and promotes the formation of uniform and fine grains. The flexible polymer chains of the polyethylene derivatives can fill dangling bonds at grain boundaries or on the surface of tin-based perovskite films, passivating defects and optimizing film quality while maintaining a relatively thin film. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0018] Figure 1 A flow chart showing a method for preparing a tin-based perovskite film according to an embodiment of the present invention is shown;

[0019] Figure 2 A cross-sectional schematic diagram of a tin-based perovskite solar cell according to an embodiment of the present invention is shown;

[0020] Figure 3 Shown are microscope images of Examples 1 and 2 of the present invention and Comparative Example 1;

[0021] Figure 4 Graphs showing the photoelectric conversion efficiency test results of tin-based perovskite solar cells according to Examples 1 to 6 of the present invention and Comparative Example 1;

[0022] Figure 5 A performance comparison chart of the tin-based perovskite solar cells of Examples 2 to 6 of the present invention is shown.

[0023] Description of reference numerals:

[0024] 1- substrate and bottom electrode;

[0025] 2-hole transport layer;

[0026] 3- Absorption layer;

[0027] 4-first electron transport layer;

[0028] 5-second electron transport layer;

[0029] 6-Counter electrode layer. DETAILED DESCRIPTION

[0030] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concept of the present invention.

[0031] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0032] In the related art, Sn-based perovskite solar cells 2+ Very easily oxidized to Sn 4+ , and is also prone to rapid crystallization, resulting in poor surface morphology of the tin-based perovskite film as the core structure, short carrier diffusion lifetime, and relatively poor crystallization morphology of the film. For example, there are holes on the surface or inside the film, which short-circuits the two sides of the film and causes photocurrent or photovoltage loss in the solar cell or device used.

[0033] The main reason is that Sn 2+The 5s orbital electronic characteristics of Sn make it easy to be oxidized and the crystallization rate is too fast. 2+ Oxidation will form tin vacancies in the perovskite, causing the tin-based perovskite film to deviate from its intrinsic properties, forming a P-doped state, and increasing the defect state density. 2+ Too fast crystallization will lead to chaotic crystallization dynamics, forming uneven and non-dense tin-based perovskite films, which may cause short circuits between the upper and lower electrodes (carrier transport layers), affect the crystallization quality, and greatly reduce device performance.

[0034] In the printing process of tin-based perovskite solar cells, the films usually prepared in the related technology are not tight, and there are many defects and holes on the surface and inside of the film, which makes the leakage current phenomenon more serious when the device is subsequently prepared. In order to obtain a better film morphology, the related technology increases the thickness of the tin-based perovskite film (for example, by increasing the concentration of the precursor), which helps to improve the integrity of the film. However, due to the increase in thickness, the mobility of the photogenerated carriers will not be enough to support their transmission to the interface, which will reduce the photocurrent density generated by the perovskite film. In addition, due to the Sn 2+ The oxidative properties of tin lead to a high defect state density, a large non-radiative recombination intensity, and a low carrier diffusion length, further hindering their transport from the perovskite to the interface between the perovskite and the carrier transport layer. Consequently, the current of related tin-based perovskite solar cells is significantly reduced, leading to device performance degradation.

[0035] In view of this, the present invention provides a tin-based perovskite film and a preparation method thereof, and a tin-based perovskite solar cell, so as to obtain a tin-based perovskite solar cell having both uniform and continuous surface morphology and better photoelectric conversion efficiency.

[0036] According to an exemplary embodiment of the present invention, the present invention provides a method for preparing a tin-based perovskite film. Figure 1 FIG. 1 shows a flow chart of a method for preparing a tin-based perovskite film according to an embodiment of the present invention, as shown in FIG. Figure 1 As shown, the preparation method includes operations S101~S102.

[0037] In operation S101 , a tin-based perovskite raw material is dissolved in an organic solvent, and a polyethylene derivative is added to prepare a tin-based perovskite precursor solution, wherein the polyethylene derivative includes at least one of polyvinyl alcohol or polyvinyl pyrrolidone.

[0038] In operation S102 , a tin-based perovskite precursor solution is coated into a film by a printing method, and an annealing treatment is performed to obtain a tin-based perovskite thin film.

[0039] According to an embodiment of the present invention, a coordination bond interaction is formed between the polyethylene derivative (polyvinyl alcohol or polyvinyl pyrrolidone) and the tin-based perovskite film, which can slow down the Sn 2+ The crystallization rate is very fast, making the surface of the tin-based perovskite film more uniform and continuous. In addition, these polyethylene derivatives provide good hydrophobicity, providing a passivation effect on the surface of the tin-based perovskite film, which helps to reduce the defect state density.

[0040] It should be noted that the coating method of the tin-based perovskite film of the present invention can be, for example, a printing method such as blade coating, spray coating, and slit coating.

[0041] According to an embodiment of the present invention, the polyethylene derivative includes at least one of polyvinyl alcohol and polyvinyl pyrrolidone. Polyvinyl alcohol has polar hydroxyl groups, while polyvinyl pyrrolidone has carbonyl groups. The hydroxyl and carbonyl groups form coordination bonds with the tin-based perovskite, slowing crystallization, passivating defects, and reducing defect density.

[0042] Preferably, the polyethylene derivative is polyvinyl pyrrolidone. When polyvinyl pyrrolidone is used, the quality of the tin-based perovskite film can be better optimized, so that the film has better density.

[0043] In some embodiments, the coating and annealing are performed under an inert atmosphere. Providing an inert atmosphere helps form a denser film structure. The inert atmosphere can be, for example, a nitrogen atmosphere, an argon atmosphere, or a mixture of the two.

[0044] In some embodiments, the mass ratio of the polyethylene derivative to the tin-based perovskite raw material is 0.01-0.3:100. This configuration can further optimize the surface quality of the tin-based perovskite film, further reduce defect density, and alleviate the exposure of the tin-based perovskite film. Exposure can be understood as the lack of continuous arrangement of the crystals that make up the tin-based perovskite film, exposing the carrier transport layer located on its bottom surface.

[0045] Optionally, the mass ratio of polyvinyl pyrrolidone to tin-based perovskite raw material is 0.01~0.3:100, for example, it can be 0.01:100, 0.05:100, 0.1:100, 0.15:100, 0.2:100, 0.25:100 or 0.3:100, etc., or a range between any two of the above values.

[0046] In some embodiments, the raw materials of tin-based perovskite include formamidine acetate, ammonium iodide, iodine powder, tin powder and stannous fluoride. When the tin-based perovskite film is annealed, the ammonium ions and acetate ions of the formamidine acetate and ammonium iodide interact to generate acetic acid and ammonia gas, which volatilize. Ammonia has reducing properties, which further protects the Sn during the annealing process. 2+, to reduce oxidation. Since acetic acid and ammonia are highly volatile, they will not remain in the crystal lattice after annealing to form impurities, further improving quality. Formamidine acetate and ammonium iodide react during annealing to form formamidine iodine, further slowing the crystallization process. Furthermore, the coordination interaction between formamidine acetate and tin iodide can also slow the rapid crystallization of tin-based perovskite films, helping to produce dense, high-quality films.

[0047] According to an embodiment of the present invention, using the above-mentioned materials as the raw materials for tin-based perovskite and combining them with polyethylene derivatives can help significantly improve the film-forming quality of the tin-based perovskite film and make the thickness of the film within a normal range, while taking into account good photoelectric performance, which is conducive to subsequent application as the core part of high-performance devices.

[0048] In some embodiments, the purity of iodine powder and tin powder is ≥99%. Materials with a purity of more than 99.99% are generally used in the related art. For example, commercially purchased stannous iodide is often used in the related art, and its cost is relatively high. The coordination between the above-mentioned materials of the present invention helps to improve the quality of the film, so that a denser film can be obtained by using iodine powder and tin powder. Since the direct use of iodine powder and tin powder can greatly reduce costs, for example, the same quality of tin-based perovskite powder raw materials, the combination of iodine powder and tin powder is about 3% of the cost of stannous iodide, reducing the cost of tin-based perovskite films, is conducive to industrial promotion. Furthermore, the purity of corresponding formamidine acetate and ammonium iodide can also be more than 99%, which can further save costs.

[0049] In some embodiments, the molar ratio of formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride is 1:1:1:1:(0.01-0.2). This configuration helps the prepared tin-based perovskite film have a higher photoelectric conversion efficiency.

[0050] Optionally, the molar ratio of formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride can be, for example, 1:1:1:1:0.01, 1:1:1:1:0.05, 1:1:1:1:0.1, or 1:1:1:1:0.2, but is not limited thereto.

[0051] In some embodiments, dissolving the tin-based perovskite raw material in an organic solvent includes: dissolving the tin-based perovskite raw material in an organic solvent at a temperature of 15 to 35°C; for example, formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride are dissolved in an organic solvent, and a polyethylene derivative is added to prepare a tin-based perovskite precursor solution. The temperature can be, for example, 15°C, 20°C, 25°C, 30°C, 35°C, etc., but is not limited thereto. Too low a temperature is not conducive to the rapid preparation of the tin-based perovskite precursor solution and the degree of perovskite dissolution. Too high a temperature will promote the oxidation of the tin material, resulting in a waste of resources. As described above, preparing the tin-based perovskite precursor solution within an appropriate temperature range helps to significantly improve the film formation effect.

[0052] In some embodiments, the organic solvent includes at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and γ-butyrolactone (GBL). For example, the organic solvent includes DMF and DMSO.

[0053] Optionally, the volume ratio of DMF to DMSO is 3:1 to 10:1, for example, 3:1, 5:1, 7:1 or 10:1, but not limited thereto. Preferably, the volume ratio of DMF to DMSO is 4:1.

[0054] In some embodiments, the annealing temperature of the annealing treatment is 60-150°C, and the annealing time is 5-30 minutes, for example, annealing at 60°C for 30 minutes, annealing at 70°C for 10 minutes, annealing at 70°C for 20 minutes, annealing at 80°C for 10 minutes, annealing at 80°C for 20 minutes, annealing at 90°C for 15 minutes, annealing at 100°C for 20 minutes, annealing at 110°C for 15 minutes, annealing at 130°C for 10 minutes, and annealing at 150°C for 20 minutes, but are not limited to the values ​​listed above. During the annealing film formation process, the solvent in the tin-based perovskite precursor solution is volatilized. Too low an annealing temperature is not conducive to crystal growth and high-quality crystals cannot be obtained, while too high an annealing temperature will directly lead to oxidative degradation of the tin-based perovskite film. Therefore, by controlling the annealing temperature and annealing time within the above requirements, a tin-based perovskite film with high surface quality can be obtained.

[0055] Optionally, the annealing temperature may be, for example, but not limited to, 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., or 150° C. The annealing time may be 5 to 30 minutes, for example, but not limited to, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0056] In some embodiments, the molar concentration of the tin-based perovskite precursor solution is 0.1-0.8 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L or 0.8 mol / L, but is not limited thereto.

[0057] In one embodiment, the preparation process of the tin-based perovskite film can be as follows:

[0058] Under an inert gas atmosphere, a tin-based perovskite precursor solution is coated on the substrate surface. During the coating process, nitrogen is extracted from the tin-based perovskite precursor solution. After coating, the substrate is annealed at the aforementioned temperature of 60-150°C to obtain a tin-based perovskite film.

[0059] Furthermore, the height of the scraper used for coating from the blade tip to the substrate surface is 5 to 100 μm, for example, 5 μm, 10 μm, 30 μm, 50 μm, 70 μm, 90 μm or 100 μm, but not limited thereto. The coating speed is 0.1 to 100 mm / s, for example, 0.1 mm / s, 0.5 mm / s, 1 mm / s, 10 mm / s, 50 mm / s, 80 mm / s or 100 mm / s, but not limited thereto. The amount of perovskite solution dripped onto the substrate surface for coating each time is 5 to 50 μL, for example, 5 μL, 10 μL, 20 μL, 30 μL, 40 μL or 50 μL, but not limited thereto.

[0060] According to an embodiment of the present invention, the present invention uses the above-mentioned tin-based perovskite raw materials and polyethylene derivatives to delay the process of perovskite in the perovskite precursor solution to form crystalline perovskite, so that the tin-based perovskite can be uniformly crystallized to obtain a high-quality, high-density and excellent morphology tin-based perovskite film.

[0061] According to the method for preparing the tin-based perovskite film according to the embodiment of the present invention, during the high-temperature annealing process of the tin-based perovskite film, the ammonium ions and acetate ions interact to generate acetic acid and ammonia gas and volatilize. Usually during annealing, the high temperature causes the solvent DMSO to oxidize part of the Sn 2+ The generated ammonia is reducing and can protect the Sn in the tin-based perovskite film during annealing. 2+Therefore, the extra components such as acetic acid and ammonia do not remain in the crystal lattice as impurities, further improving the film quality of the film. When formamidine acetate and ammonium iodide are annealed again, FAI is formed by reaction, which slows down the rate of crystallization. At the same time, formamidine acetate can also form a coordination with SnI2, slowing down the problem of too fast crystallization of tin-based perovskite films, improving crystallization kinetics, and obtaining high-quality tin-based perovskite films. Furthermore, polyvinyl pyrrolidone, as a polymer, has a quantum confinement effect, which further reduces the crystallization rate of perovskite. Polyvinyl pyrrolidone can serve as a template to provide heterogeneous nucleation sites for perovskite, and the material can provide hydrophobic protection in perovskite. Polyvinyl pyrrolidone has a large number of hydrogen bonds that passivate the perovskite surface, which helps to reduce the defect state density.

[0062] According to another exemplary embodiment of the present invention, the present invention provides a tin-based perovskite film obtained by the above-mentioned preparation method.

[0063] According to an embodiment of the present invention, a tin-based perovskite precursor solution containing a polyethylene derivative and a tin-based perovskite raw material is used to delay Sn 2+ crystallization process, and can inhibit Sn 2+ The oxidation of tin-based perovskite films can be improved, thereby improving the film quality and density of the films, thereby improving the photoelectric conversion efficiency.

[0064] Furthermore, the raw materials and proportions of the tin-based perovskite precursor solution are the same as those described above and will not be repeated here.

[0065] Preferably, the thickness of the tin-based perovskite film is 100-200 nm, for example, 100 nm, 150 nm, or 200 nm, but not limited thereto. Due to the coordination between the polyethylene derivative and other materials in the tin-based perovskite raw material, the tin-based perovskite film can achieve improved photoelectric conversion efficiency with little increase in thickness, facilitating industrial promotion.

[0066] According to another exemplary embodiment of the present invention, the present invention provides a tin-based perovskite solar cell, comprising a light-absorbing layer, wherein the light-absorbing layer comprises the above-mentioned tin-based perovskite film.

[0067] Figure 2 A cross-sectional schematic diagram of a tin-based perovskite solar cell according to an embodiment of the present invention is shown.

[0068] refer to Figure 2 As shown, the tin-based perovskite solar cell is arranged on a substrate and a bottom electrode 1, and the tin-based perovskite solar cell includes a hole transport layer 2, an absorption layer 3, a first electron transport layer 4, a second electron transport layer 5 and a counter electrode layer 6 stacked in sequence.

[0069] In some embodiments, the substrate and the bottom electrode 1 may be glass with an indium tin oxide (ITO) thin film coated on the surface.

[0070] In some embodiments, the hole transport layer 2 may be poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS). Furthermore, the hole transport layer 2 may have a thickness of 30 to 50 nm.

[0071] In some embodiments, the absorption layer 3 may be a tin-based perovskite film; further, the absorption layer 3 may have a thickness of 100-200 nm.

[0072] In some embodiments, the first electron transport layer 4 may be a fullerene (C 60 ); Further, the thickness of the first electron transport layer 4 can be 10~30nm.

[0073] In some embodiments, the second electron transport layer 5 may be 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP); further, the thickness of the second electron transport layer 5 may be 1-10 nm.

[0074] In some embodiments, the counter electrode layer 6 may be silver with a thickness of 80-120 nm.

[0075] The following schematically illustrates the tin-based perovskite thin film and its preparation method, and the tin-based perovskite solar cell. It should be noted that this example is only a specific embodiment of the present invention and does not limit the scope of protection of the present invention.

[0076] Comparative Example 1:

[0077] An ITO transparent conductive substrate (length × width: 15 × 15 mm) was ultrasonically cleaned in deionized water, glass cleaner, acetone, isopropyl alcohol, and ethanol solutions in sequence, and cleaned in each solvent for 15 minutes. The substrate was dried in a constant temperature oven at 70 degrees for more than 3 hours. The cleaned conductive substrate was treated under ultraviolet ozone conditions for 15 minutes to obtain a clean ITO transparent conductive substrate for standby use.

[0078] Using a pipette, 10 μL of an aqueous dispersion of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) was spin-coated onto the treated ITO transparent conductive substrate using a spin coater. The spin-coating process parameters were: 5000 rpm for 40 seconds. After spin coating, the substrate was heated on a 150°C hotplate for 10 minutes to form a hole transport layer. All preparation processes were performed in a low-humidity (below 10% RH) air glove box.

[0079] Formamidine hydroiodide (FAI), stannous iodide (SnI2), and stannous fluoride (SnF2) were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 4:1 in a molar ratio of 1:1:1:0.1. The resulting mixed solution had a concentration of 0.3M and was placed on an oscillator and shaken at 1000 rpm for 1 hour to obtain a FASnI3 perovskite precursor solution.

[0080] In a nitrogen-filled glove box, 30 μL of the prepared perovskite precursor solution was pipetted onto the surface of an ITO transparent conductive substrate. The precursor was then evenly printed onto the prepared hole transport layer using a doctor blade. The printing process parameters were: a 20 μm blade-to-substrate height and a speed of 10 mm / s. After coating, nitrogen was blown across the surface to produce an initial tin-based perovskite film. This initial tin-based perovskite film was then annealed at 80°C in a nitrogen atmosphere for 10 minutes to produce a tin-based perovskite film.

[0081] The tin-based perovskite film was transferred to a thermal evaporation device and heated to 2×10 -4 Electron transport layer C is deposited on tin-based perovskite film under vacuum environment 60 , thickness is 20nm; in C 60 A barrier layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was then deposited to a thickness of 5 nm.

[0082] An Ag electrode was prepared on the prepared BCP barrier layer by thermal evaporation to form a counter electrode. The thickness of the counter electrode layer was 100 nm.

[0083] Example 1:

[0084] The preparation process of Example 1 is substantially the same as that of Comparative Example 1, except that polyvinyl pyrrolidone in an amount of 0.1% by weight of the tin-based perovskite raw material is further added to the prepared perovskite precursor solution.

[0085] Example 2:

[0086] The preparation process of this Example 2 is substantially the same as that of Comparative Example 1, except that in the prepared perovskite precursor solution, the molar ratio of 1:1:1:0.1 of formamidine hydroiodide (FAI), stannous iodide (SnI2), and stannous fluoride (SnF2) in Comparative Example 1 is replaced by a molar ratio of 1:1:1:1:0.1 of formamidine acetate (FAAc), ammonium iodide (NH4I), tin powder (Sn), iodine powder (I2), and stannous fluoride (SnF2), and then 0.05% of the mass of the tin-based perovskite raw material of polyvinyl pyrrolidone is added.

[0087] Figure 3The microscope images of Examples 1 and 2 of the present invention and Comparative Example 1 are shown, wherein (a) is the microscope image of Comparative Example 1, specifically, the large image on the upper left is the reflection mode of the microscope image, and the small image on the lower right is the transmission mode of the microscope image; (b) is the microscope image of Example 1, specifically, the large image on the upper left is the reflection mode of the microscope image, and the small image on the lower right is the transmission mode of the microscope image; (c) is the microscope image of Example 2, specifically, the large image on the upper left is the reflection mode of the microscope image, and the small image on the lower right is the transmission mode of the microscope image. Figure 3 From the comparison between (a) and (b), we can see that the comparison of images before and after adding polyvinyl pyrrolidone (PVP) to the perovskite made of formamidine iodide and stannous iodide shows that PVP can alleviate the bottom exposure of the tin-based perovskite film to a certain extent. Figure 3 From the comparison between (a) and (c), it can be seen that when the raw materials such as formamidine iodide and stannous iodide in the perovskite in Example 2 are replaced with formamidine acetate, amine iodide, iodine powder, tin powder and polyvinyl pyrrolidone, the film of Example 2 is uniform and dense, and the transmission image further proves that it is dense and opaque, and there are no holes.

[0088] Example 3:

[0089] The preparation process of Example 3 is substantially the same as that of Example 2, except that 0.1% of polyvinyl pyrrolidone by weight of the tin-based perovskite raw material is added.

[0090] Example 4:

[0091] The preparation process of Example 4 is substantially the same as that of Example 2, except that 0.15% of the mass of the tin-based perovskite raw material of polyvinyl pyrrolidone is added.

[0092] Example 5:

[0093] The preparation process of this Example 5 is substantially the same as that of Example 2, except that 0.2% of the mass of the tin-based perovskite raw material of polyvinyl pyrrolidone is added.

[0094] Example 6:

[0095] The preparation process of Example 6 is substantially the same as that of Example 2, except that 0.25% of the mass of the tin-based perovskite raw material of polyvinyl pyrrolidone is added.

[0096] The photoelectric conversion efficiency and cell performance of the tin-based perovskite solar cells of Examples 1 to 6 and Comparative Example 1 were tested, and the test results are shown in Table 1 below.

[0097] Table 1

[0098]

[0099] Figure 4The photoelectric conversion efficiency test results of the tin-based perovskite solar cells of Examples 1 to 6 of the present invention and Comparative Example 1 are shown, wherein (a) is a current density-voltage curve of Example 1 (with PVP) and Comparative Example 1 (without PVP); (b) is a current density-voltage curve of Examples 2 to 6. Figure 4 As shown in (a) and (b) in the figure, according to the comparative examples and embodiments of the present invention, by regulating the raw materials and dosage in the tin-based precursor solution, a tin-based perovskite thin film with better film quality and a tin-based perovskite solar cell with better photoelectric conversion efficiency can be obtained.

[0100] Compared with Comparative Example 1 in which no polyvinyl pyrrolidone is added, Example 1 uses polyvinyl pyrrolidone to prepare the tin-based perovskite precursor solution, so that the prepared tin-based perovskite solar cell has better perovskite film quality and device performance.

[0101] Figure 5 Performance comparison graphs of tin-based perovskite solar cells of Examples 2 to 6 of the present invention are shown, wherein (a) is a graph showing the change of open circuit voltage with the dosage of polyvinyl pyrrolidone; (b) is a graph showing the change of current density with the dosage of polyvinyl pyrrolidone; (c) is a graph showing the change of fill factor with the dosage of polyvinyl pyrrolidone; and (d) is a graph showing the change of photoelectric conversion efficiency with the dosage of polyvinyl pyrrolidone.

[0102] Refer to Table 1 and Figure 5 As shown, according to the above comparative examples and embodiments of the present invention, by regulating the raw materials and their ratios in the tin-based precursor solution, tin-based perovskite films with better film quality and tin-based perovskite solar cells with better photoelectric conversion efficiency can be obtained.

[0103] Among them, compared with Comparative Example 1 which does not add polyvinyl pyrrolidone and uses conventional perovskite precursor materials, Example 1 uses polyvinyl pyrrolidone to prepare a tin-based perovskite precursor solution, so that although the current density of the prepared tin-based perovskite film is basically not much different from that of Comparative Example 1, its open circuit voltage is higher and the battery performance is relatively better. Comparing Example 1 and Example 2, Example 2 uses polyvinyl pyrrolidone and the specific precursor material system of the present invention to synergistically greatly improve the performance of the tin-based perovskite battery. The various performances of the solar cells in Examples 2 to 6 are all improved to varying degrees compared to Example 1.

[0104] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a tin-based perovskite film, comprising: Dissolving a tin-based perovskite raw material in an organic solvent and adding a polyethylene derivative to prepare a tin-based perovskite precursor solution; wherein the polyethylene derivative includes at least one of polyvinyl alcohol and polyvinyl pyrrolidone; and The tin-based perovskite precursor solution is coated into a film by a printing method, and the tin-based perovskite film is obtained after annealing treatment.

2. The preparation method according to claim 1, wherein The coating film formation and annealing treatment are performed under an inert atmosphere.

3. The preparation method according to claim 1 or 2, wherein The mass ratio of the polyethylene derivative to the tin-based perovskite raw material is 0.01-0.3:

100.

4. The preparation method according to claim 3, wherein The tin-based perovskite raw materials include formamidine acetate, ammonium iodide, iodine powder, tin powder and stannous fluoride.

5. The preparation method according to claim 4, wherein The purity of iodine powder and tin powder is ≥99%.

6. The preparation method according to claim 4, wherein The molar ratio of formamidine acetate, ammonium iodide, iodine powder, tin powder, and stannous fluoride is 1:1:1:1:(0.01~0.2).

7. The preparation method according to claim 1, wherein The step of dissolving the tin-based perovskite raw material in an organic solvent comprises: Dissolving the tin-based perovskite raw material in an organic solvent at a temperature of 15-35°C; The organic solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, and γ-butyrolactone.

8. The preparation method according to claim 1, wherein The annealing temperature of the annealing treatment is 60~150℃, and the annealing time is 5~30min.

9. A tin-based perovskite film obtained by the preparation method according to any one of claims 1 to 8; Preferably, the thickness of the tin-based perovskite film is 100-200 nm.

10. A tin-based perovskite solar cell comprising a light-absorbing layer, wherein the light-absorbing layer comprises the tin-based perovskite thin film according to claim 9.

Citation Information

Cited By

  • Preparation method of perovskite precursor solution and anti-radiation perovskite thin film

    CN121692971A